Pengaruh Sosialisasi Perpajakan dan Ekstensifikasi Pajak terhadap Penerimaan Pajak Penghasilan Orang Pribadi - suyanto suyanto; Kiftia Yahya (Jurnal Ekonomi Akuntansi dan Manajemen, 2016)
This research aims to test the tax socialization on tax revenues. This research also aims to The tax extension on tax revenues. This research was conducted at the tax office pratama Wonosari.This research was conducted using saturated sample with a sample of 65 respondents sample that may be analyzed about 63 questionnaire. The analysis data method of this research was multiple linear regression. This research was quantitative. The data used in this study are primary data.